Maros Pucak Botanical Garden Tourism Development Strategy - R. Yudha; Nursyamsi; N. Nurdin; A. Tuwo; A. Bahar; AR. Rasyid (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Tadulako, 2022)
Tourism in the Pucak Botanical Gardens which is managed by the Provincial Government of South Sulawesi has not experienced significant development even though it has had a master plan since 2006. The undeveloped tourism in the Pucak Botanical Gardens certainly requires serious efforts, especially from the government and other related parties to encourage this development. Because, whether or not tourism develops in the Pucak Botanical Gardens will affect the development of tourism in Maros Regency in particular and South Sulawesi Province in general. But until now. This study aims to determine the tourism development strategy in Pucak Botanical Gardens through concrete and strategic steps. The tourism development strategy is carried out by identifying strengths, weaknesses, opportunities and threats through SWOT analysis. The result of the analysis of the Pucak Botanical Gardens tourism development strategy is the SO strategy which is formulated as follows: (1) Making the Pucak Botanical Gardens a leading tourist destination that has easy accessibility; (2) The Pucak Botanical Gardens area has a varied topography, the distance to tourist attractions that are close to the city of Makassar, the availability of clean water sources in the area, relatively cheap costs and conducive security make many tourists who want to visit supported by the many lodgings around Puncak Botanical Gardens; (3) The Pucak Botanical Gardens tourism product development plan/program is prepared and implemented every year aimed at increasing products and attractions by utilizing existing potentials, tourism supporting infrastructure and cooperation with other parties in the development of tourist attractions and facilities and infrastructure, capacity building HR manager of the Pucak Botanical Gardens.